ASSESSMENT OF PHYSICAL AND CHEMICAL SOIL PROPERTIES IN URBAN GREEN AREAS OF NOVI GRAD MUNICIPALITY, SARAJEVO CANTON (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Modern urbanization trends are increasing population density in cities and suburban areas, posing challenges to environmental quality. Urban soils play a crucial role in supporting ecological functions such as water filtration, carbon storage, and biodiversity maintenance. Despite this, they are often subject to anthropogenic pressures that degrade their structure and functionality. While soil research has traditionally focused on agricultural and forest lands, urban soils-particularly in Bosnia and Herzegovina remain understudied, especially regarding contamination by heavy metals and other pollutants. This study investigates the condition of soils at three urban green locations in the Novi Grad municipality, Sarajevo Canton, under different land uses (lawn, tree-covered, arable). The results show that soils are predominantly sandy and carbonate, with slightly alkaline pH. Humus content ranges from 3.3 to 4.19%, while carbon stocks vary from 6.8 kg/m² (lawn) to 8.1 kg/m² (tree-covered areas). The soils are moderately to well supplied with nitrogen (average C/N ratio of 13:1), moderately supplied with available potassium, and poorly supplied with available phosphorus. Filtration properties are generally poor to moderate, with an average water retention capacity of 43.96% vol. Importantly, all soil samples contained heavy metals below harmful concentration thresholds, as defined by national standards. These findings can inform improved urban soil management strategies in the Sarajevo Canton.